Adversity Quotient and Students’ Mathematical Reasoning, Communication, and Connection Abilities: A PLS-SEM Analysis - Destiani, Sinta; Rinaldi, Achi; Pitri, Rizka (Desimal: Jurnal Matematika, 2026)
Mathematical reasoning, communication, and connection are essential competencies for meaningful mathematics learning, yet their development may also depend on how students respond to academic difficulty. This study examined the structural relationships between Adversity Quotient (AQ) and students’ mathematical reasoning, communication, and connection abilities, including the direct and indirect pathways among these constructs. A quantitative cross-sectional design using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed with 106 seventh-grade students at SMPN 1 Natar, Lampung, Indonesia. Data were collected using an AQ questionnaire and a 15-item social-arithmetic test assessing mathematical reasoning, communication, and connection abilities, and were analyzed using SmartPLS 3.0. The results showed that AQ was positively associated with mathematical communication (β = 0.573, p < .001) but was not significantly associated with mathematical reasoning (β = -0.139, p = .183) or mathematical connection (β = -0.071, p = .399). Mathematical reasoning was positively associated with communication (β = 0.390, p < .001), while communication showed the strongest direct relationship with connection (β = 0.712, p < .001). Significant indirect effects were found for AQ on connection through communication (β = 0.408, p < .001) and for reasoning on connection through communication (β = 0.278, p < .001). These findings identify mathematical communication as a central structural bridge linking adversity-related responses and reasoning with students’ ability to establish mathematical connections, offering an integrated perspective on affective and cognitive processes in mathematics learning, particularly within lower-secondary mathematics education in Indonesia.